جهود محمد بن بريكة في خدمة التصوف الإسلامي - بحري, حكيمة; محده, سكينة (University of Eloued جامعة الجزائر, 2020)
لا ريب أن لعلم التصوف الاسلامي مكانة عظيمة ,كيف لا وهو علم شرعي مختص ومهتم بجوهر الدين , الركن الثالث من أركان الاسلام "ان تعبد الله كأنك تراه ,فان لم تكن تراه فهو يراك" وقد بذل العلماء قديما وحديثا جهودا كبيرة في تأسيس له وشرع معانيه ومضامينه الروحية. من اجل هذا جعلنا بحثنا حول جهود الاستاذ المختص في شأن الصوفي محمد بن بريكة- رحمه الله تعالى- في خدمته للتصوف الاسلامي حيث بدأناه بمقدمة بعناصرها , وقسمنا العرض لثلاث مباحث اجبنا فيها على الاشكالية الرئيسة المطروحة حوله, وهي :ماهي ابرز جهود محمد بن بريكة, في خدمة التصوف الاسلامي؟ اما المبحث الاول فقد خصصناه لتعريف بالتصوف الاسلامي لغتا واصطلاحا مع اهميته ونشأته واطواره ومصادره ومؤشراته ,والمبحث الثاني تناولنا فيه نبذة عن الدكتور محمد بن بريكة ابتداء من اسمه ونسبه واخلاقه الى سيرته العلمية واتجاهه لتصوف ووفاته وآثاره ومكانته , والمبحث الاخير جعلناه لجهوده لخدمت التصوف الاسلامي من خلال نشره في المجتمع الغربي ونشره في المجتمع الجزائري وجهوده في اصلاحه, ودفاعه عن التصوف ,ومواجهته لأمراض العصر , كفساد الاخلاق والعولمة من خلاله سواء عن طريق الكتابة او تأليف او عن طريق الدروس والمحاضرات, ثم ختمناه بخاتمة فيها اهم النتائج التوصيات . There is no doubt that the science of Islamic mysticism has a great position, how not, and it is a specialized Sharia science concerned with the essence of religion. The third pillar of Islam is: “If you worship God as if you see Him, and if you do not see Him, then He sees you.” And its spiritual implications. It is for this reason that we made our discussion about the efforts of the professor specializing in the matter of the Sufi mystic Muhammad bin Barika - may God Almighty have mercy on him - in his service for Islamic mysticism We started with an introduction with its elements, and we divided the presentation into three sections in which we answered the main problem raised around it, namely: What are the most prominent efforts of Muhammad bin Barika in the service of Islamic mysticism? As for the first topic, we devoted it to defining Islamic mysticism, both linguistically and idiomatically, with its importance, origins, phases, sources, and indicators, and the second study dealt with a brief about Dr. Muhammad bin Barika starting from his name, attribution, morals to his scientific biography and his tendency to Sufism, his death, effects and standing, and the last study we made for his efforts to serve Islamic mysticism through Disseminating it in Western society and publishing it in Algerian society and its efforts in reforming it, defending Sufism, and facing the diseases of the age, such as corruption of morals and globalization through it, whether by writing or writing or through lessons and lectures, then we concluded with a conclusion with the most important results and recommendations
مذكرة ماستر تخصص عقيدة
Keywords: جهود - محمد - بريكة - خدمة - التصوف - الإسلامي; Efforts - Muhammad - Barika - service - Soufisme - Islamique